Carbon-dot-decorated TiO2 nanotube arrays used for photo/voltage-induced organic pollutant degradation and the inactivation of bacteria. (12th February 2016) - Feng, Lingyan; Sun, Hanjun; Ren, Jinsong; Qu, Xiaogang
Abstract: Photoluminescent carbon dots (c-dots) have recently attracted growing interest as a new member of the carbon-nanomaterial family. Here, we report for the first time that c-dot-decorated TiO2 nanotube arrays (c-dot/TiNTs) exhibit highly enhanced abilities regarding photo/voltage-induced organic pollutant degradation and bacterial inactivation. By applying UV irradiation (365 nm) or an electrochemical potential over 3 V (versus Ag/AgCl), an organic dye and a herbicide were efficiently degraded. Moreover, the inactivation of Gram-positive S. aureus and Gram-negative E. coli bacteria was realized on a c-dot/TiNT film. The c-dots were able to absorb light efficiently resulting in multiple exciton generation and also a reduction in the recombination of the e − /h + pair produced in c-dot/TiNT film during photo/voltage-induced degradation. It was also possible to readily regenerate the surface using ultraviolet light irradiation, leaving the whole film structure undamaged and with high reproducibility and stability.